Needs Analysis-Based Teaching Materials Develoment for English Speaking Skill Course in Tertiary Level of Education - Kaharuddin, Kaharuddin (Journal of Education Review Provision, 2025)
English is a compulsory subject for students in Indonesia. However, the English learning process is often not concordant with the needs and level of students. The development of English learning materials is not based on needs analysis, but based on the instincts of lecturers so that their effectiveness to help students master English is not reliable. This research was conducted to explain the benefits of using needs analysis to develop the materials of English teaching in university. 137 respondents were determined purposively. The research data were obtained by questionnaire distribution. The data analysis technique was descriptive technique. This research was conducted by using the development method with three systematic phases. 1) Input phase: conducting analysis of students’ needs, 2) development phase: formulating English learning goals and objectives which become the basis for determining and developing course content, and 3) output phase: creating draft lesson plans and prototype learning materials. This research produces a methodology for developing English learning materials where a learning plan and prototype for a needs-based English learning unit are obtained. The methodology of this teaching materials development can be used by lecturers in creating teaching materials for other English courses they teach.